Unraveling the Drivers of Inequality in Maternal Healthcare Utilization in Indonesia: A Decomposition Analysis - Wahyuningsih, Wji; Siregar, Kemal N; Nurhakiki, Syifa (UI Scholars Hub, 2025)
This study assessed socioeconomic inequalities in maternal healthcare utilization in Indonesia and identifies key factors driving these inequalities. We used data from 2013 and 2023 Indonesian Health Surveys, comprised of a total unweighted sample of 15,638 and 9,923 women aged 15-49 in the 2013 and 2023, respectively. Concentration index (CI) measured wealth-based inequality, and decomposition analysis identified primary drivers of inequalities in maternal healthcare access. Overall maternal healthcare service utilization has increased, but significant inequalities persist. Antenatal care showed minimal improvement, with the CI rising from 0.059 to 0.079, indicating a persistent higher socioeconomic distribution. Facility-based deliveries improved, with the CI decreasing from 0.115 to 0.039. Cesarean section inequality, though reduced, remains high, with CI declining from 0.299 to 0.158. Decomposition analysis revealed that socioeconomic status, women’s education, and geographic location were the primary drivers of inequalities in maternal healthcare utilization. While Indonesia has made progress in increasing facility-based deliveries, especially among the poorest women, inequalities persist in antenatal care and cesarean section. Pro-poor policies must address these multidimensional barriers by improving access to education, particularly for women, and implementing region-specific interventions, especially in eastern Indonesia, which lags in healthcare development.